2017
DOI: 10.1111/are.13395
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of fatty acid transport proteins in Japanese seabassLateolabrax japonicus, and their gene expressions in response to dietary arachidonic acid

Abstract: In this study, putative cDNA of three fatty acid transport protein (FATP) isoforms, that is FATP1, FATP4 and FATP6, was cloned and characterized from the liver of Japanese seabass (Lateolabrax japonicus), and their expression in response to diets with different arachidonic acid (ARA) levels (0.05%, 0.22%, 0.37%, 0.60%, 1.38% and 2.32% of dry matter) was investigated through a feeding trial. Two subtypes of FATP1, that is FATP1a and FATP1b, were cloned for the first time. The Japanese seabass FATPs showed high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…FXR, Farnesoid X receptor; LXR, liver X receptor; TGR5, G-protein-coupled bile acid receptor-1. (Kaitetzidou et al, 2015;Xu et al, 2017). In this study, the supplement of bile acids (0.3%) significantly increased fish intestine FABP2 gene expression.…”
Section: Discussionsupporting
confidence: 48%
“…FXR, Farnesoid X receptor; LXR, liver X receptor; TGR5, G-protein-coupled bile acid receptor-1. (Kaitetzidou et al, 2015;Xu et al, 2017). In this study, the supplement of bile acids (0.3%) significantly increased fish intestine FABP2 gene expression.…”
Section: Discussionsupporting
confidence: 48%
“…FATP are key proteins in cellular uptake and metabolism of long and very long-chain fatty acids, whereas FABP plays important roles in intracellular lipid uptake and overall lipid homeostasis. 202,203 In European sea bass, Torrecillas et al observed that with reduced dietary ARA levels (0.2%-1.4% d.w. or 1.0%-6.0% TFA), hepatic lipid (1) COX seems to prefer ARA as substrate.…”
Section: Functions In Lipid Metabolism Regulationmentioning
confidence: 99%
“…In fact, varying and contrasting results were also observed regarding the effects of dietary ARA on gene expression of various subtypes of fatty acid transport proteins (FATP) and fatty acid‐binding proteins (FABP). FATP are key proteins in cellular uptake and metabolism of long and very long‐chain fatty acids, whereas FABP plays important roles in intracellular lipid uptake and overall lipid homeostasis 202,203 …”
Section: Functions Of Ara In Fishmentioning
confidence: 99%